2021
DOI: 10.7717/peerj.10776
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C supplementation reduces expression of circulating miR-451a in subjects with poorly controlled type 2 diabetes mellitus and high oxidative stress

Abstract: Background Vitamin C is an essential element required for normal metabolic function. We investigated the effect of vitamin C supplementation on circulating miRNA (miR) expression in subjects with poorly controlled type 2 diabetes mellitus (T2DM). Changes in miR expression were also correlated with clinical measures of disease. Methods Pre- and post-vitamin C supplementation samples from five participants who had increased vitamin C levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…The latter, previously described for its ability to induce EndMT in diabetic mouse heart ( Liang et al, 2019 ), has been recently reported to be up-regulated in diabetic subjects with high oxidative stress. The association between miR-451 and oxidative stress has been further confirmed with the use of the antioxidant Vitamin C; indeed, Vitamin C administration in diabetic subjects decreased both the expression of miR-451 and ROS levels ( Ruknarong et al, 2021 ). Finally, an interplay being the basis of mitochondrial functions in kidney ECs involves the miR-let-7 family, (FGF)/FGFR1 signaling pathway and SIRT3 ( Srivastava et al, 2020c ).…”
Section: Potential Ros-endmt-small Rnas Interplay In Diabetes-associated Fibrotic Conditionsmentioning
confidence: 84%
See 1 more Smart Citation
“…The latter, previously described for its ability to induce EndMT in diabetic mouse heart ( Liang et al, 2019 ), has been recently reported to be up-regulated in diabetic subjects with high oxidative stress. The association between miR-451 and oxidative stress has been further confirmed with the use of the antioxidant Vitamin C; indeed, Vitamin C administration in diabetic subjects decreased both the expression of miR-451 and ROS levels ( Ruknarong et al, 2021 ). Finally, an interplay being the basis of mitochondrial functions in kidney ECs involves the miR-let-7 family, (FGF)/FGFR1 signaling pathway and SIRT3 ( Srivastava et al, 2020c ).…”
Section: Potential Ros-endmt-small Rnas Interplay In Diabetes-associated Fibrotic Conditionsmentioning
confidence: 84%
“…The miR-200 family, the anti-fibrotic activity of which has been described both in diabetic nephropathy and retinopathy, has also been shown to be associated with a decrease in oxidative stress in diabetes; specifically, the antioxidant effect of miR-200 is exerted by silencing the O-GlcNAc transferase, also known as OGT, whose enzymatic activity is associated with diabetic complications and endothelial inflammation ( Qadir et al, 2019 ). Another proof of the oxidative stress-small RNAs-EndMT interconnection comes from a study investigating the activity of miR-451 ( Ruknarong et al, 2021 ). The latter, previously described for its ability to induce EndMT in diabetic mouse heart ( Liang et al, 2019 ), has been recently reported to be up-regulated in diabetic subjects with high oxidative stress.…”
Section: Potential Ros-endmt-small Rnas Interplay In Diabetes-associated Fibrotic Conditionsmentioning
confidence: 99%
“…In a study consisting of 34 female participants with type 2 diabetes, the oral supplementation of α-tocopherol (800 IU/day) to 13 participants for 6 weeks resulted in the decrease in MDA erythrocyte level, if compared to a group (n = 21) without α-tocopherol administration [ 230 ]. In another study, 5 participants with diabetes mellitus type 2 who received vitamin C (1000 mg/day) for 6 weeks, showed decreased plasma levels of MDA and F 2 -isoprostanes, if compared to results before supplementation [ 231 ]. In a group of 40 participants with clinically diagnosed DMT2, hypoglycemic drug-administered diabetic (27 macrovascular, 13 microvascular) patients supplemented for 3 months with vitamin E (400 mg/day) showed decreased MDA serum concentration and increased serum SOD activity and erythrocyte GSH content, if compared to the beginning of study, or when compared with 40 DMT2 patients treated for 3 months with hypoglycemic drugs but without VitE supplementation [ 232 ].…”
Section: Vitamins As Antioxidantsmentioning
confidence: 99%
“… 1 —if compared to the beginning of the study; 2 —if compared to profile without antioxidant used; C1 —if compared to control: normoglycemic profile; C2 —if compared to control: healthy subjects; I —if compared to lower intake of antioxidants; Measurement methods of oxidative stress biomarkers: MDA: TBA; LHP: FOX assay; F 2 -Isoprostanes: GC-MS [ 227 ], Radioimmunoassay [ 229 ], ELISA [ 231 ]. …”
Section: Figurementioning
confidence: 99%
“…A 6‐month dietary vitamin E deficiency diet lowered hepatic miR‐122 and miR‐125b expression in freshly weaned rats, resulting in enhanced oxidative stress and inflammatory responses 10 . A recent human clinical study found that vitamin C supplementation given to T2D patients for 6 weeks down‐regulated circulating miR‐451a levels to reduce oxidative stress, suggesting that circulating miR‐451a levels can serve as a biomarker of oxidative stress 11 . Similarly, whole grain highland barley significantly suppressed the expression of the liver miRNA‐126a and miRNA‐29a in db/db mice, both of which are thought to target the gene expression of insulin receptor substrate 1 (IRS‐1)/PI3K 12 .…”
Section: Introductionmentioning
confidence: 99%